Low Prevalence of CpG Island Methylator Phenotype (CIMP) in Ugandan Colorectal Cancer: A Molecular and Clinicopathological Analysis - Wismayer, Richard; Matthews, Rosie; Whalley, Celina; Kiwanuka, Julius; Kakembo, Fredrick Elishama; Thorn, Steve; Wabinga, Henry; Odida, Michael; Tomlinson, Ian (Disease and Health: Research Developments Vol. 9, 2025)
Introduction: Genetic and epigenetic aberrations are responsible for the development of colorectal cancer (CRC) that are inherited or gained during life, or both. A number of risk factors for CRC have been determined in epidemiologic studies which include age, obesity, race, diet, cigarette smoking, inflammatory bowel disease, family history of colon cancer, intake of alcohol and physical inactivity. A recognized subgroup of colorectal cancer (CRC) known as CpG island methylator phenotype (CIMP) is associated with particular patient outcomes and genetic defects in developed high-income countries. CIMP is a well-defined epigenetic subtype in CRC, but its prevalence in African populations remains understudied. In Uganda, the CIMP status of colorectal cancer has not been determined despite the increase in the incidence of CRC according to the Kampala Cancer Registry. Hence the objective of this cross-sectional study was to determine the CIMP status of colorectal cancer in Ugandan patients. Methodology: This was a retrospective study carried out between 2008 and 2021 involving formalin fixed paraffin embedded CRC tissue blocks. Next-generation sequencing (NGS) was used to interrogate pathogenic variants which were present in the MMR genes, BRAFV600E and KRAS. The MSI status was also obtained using immunohistochemistry on MLH1, MSH2, MSH6 and PMS2. Targeted NextGen Bisulphite Sequencing was used for CIMP testing based on a validated quantitative DNA methylation assay. We analyzed CIMP status in 92 CRC patients using a 13-gene panel which included APC, CACNA1G (MINT31), CDKN2A, CRABP1, IGF2, IGFBP3, MGMT, RASSF1, SEPTIN9, SFRP2, SOCS1, SV2C(MINT 1), TMEFF1(HPP1), and WIFI. CIMP was defined as \(\ge\)6/13 methylated genes. Results: Out of 92 cases which had an adequate quantity of DNA to carry out CIMP analysis, 11(11.9%) were CIMP positive and 81(88.0%) were CIMP negative. CIMP-positive tumours represented 3(5.8%) of MSI-positive tumours compared with 8(10.7%) of MSS tumours and this did not reach statistical significance (p=0.516). CIMP was associated with BRAF mutation (p=0.013). There were 7(11.1%) CIMP-positive tumours in the left colon and 4(13.8%) CIMP-positive tumours in the right colon and this did not reach statistical significance (p=0.713). There were 5(3.9%) colorectal tumours having pathologic missense BRAF V600 mutations and 8(6.3%) colorectal tumours having pathologic missense KRAS mutations. Conclusions: In contrast to Western studies, Ugandan colorectal tumours exhibited low BRAF and KRAS mutation rates. There was a lack of association between MSI and CIMP which differs from global trends. However, in keeping with studies from the West, there was an association between CIMP and BRAF mutation. Compared to Western developed high-income countries, in Uganda the prevalence of CIMP-positive tumours is low. CIMP is a distinct epigenetic subtype of colorectal cancer in Ugandan patients. The low CIMP prevalence suggests potential ethnic or regional variations in CRC pathogenesis, warranting further study.